Unidades técnico-científicas da Polícia Federal: um estudo de caso do processo de descentralização da perícia criminal federal - Mesquita, Lidiane Kelly Coelho de (2013)
This work focused in the identification and analysis of the planning and implementation of Federal Police Department Forensics decentralization process and also in pinpointing reasons and effects of the deviation between what was planned and implemented. A theory review preceded the analysis of data acquired through field research consisted of eight interviews, five with the planners and implementers of decentralization process and three with people in charge of three decentralized units. The decentralization process planning was carried out by teams of intermediate level authority in the Federal Police Department. According to a research undertaken by these planners, it was detected a high demand for forensic assistance in investigations carried out in cities far from state capitals, where there was the only forensic unit available in each state. The long distance from these cities to the state capitals, and the limited resources available in the state forensic unit prevented timely fulfilling of requests, endangering the effectiveness of police investigation. These aspects together with the identification of the most demanded expertise, number of requests, local available infrastructure, and others peculiarities concerning assistance required, helped to settle parameters to identify cities where new decentralized forensic units would be raised and their characteristics. The parameters set to design decentralized units, like infrastructure, manpower and equipment were later loosened as a response for the lack of enough financial resources. As a result, some units were established without proper installations, manpower, and in sites that did not fit the selection criteria. These aspects indicate that implementation plan was set without the due and previous examination of its weaknesses, strengths, opportunities and obstacles. The lack of involvement of Federal Police senior management may explain some of the shortcomings observed. While decentralization has improved the conditions for the performance of police investigation teams, lots of weaknesses have to be addressed to ensure better effectiveness of forensic work. In conclusion, it is necessary a whole review of the decentralization process so that the necessary adjustments to improve the operating conditions of the technical-scientific decentralized units may be identified and addressed.